Triple tracer (blue dye, indocyanine green, and Tc99) compared to double tracer (indocyanine green and Tc99) for sentinel lymph node detection in endometrial cancer: a prospective study with random assignment. Issue 7 (17th July 2019) - Kessous, Roy; How, Jeffrey; Abitbol, Jeremie; Puzhakkal, Sanam; Kogan, Liron; Yasmeen, Amber; Salvador, Shannon; Gotlieb, Walter H; Lau, Susie
Abstract : Objective: Sentinel lymph node (SLN) mapping is increasingly being used in the treatment of apparent early-stage endometrial cancer. The aim of this study was to evaluate whether three tracers (blue dye, indocyanine green (ICG), and technetium-99 (Tc99)) performed better than two (ICG and Tc99). Study Design: Prospective study of all consecutive patients (n=163) diagnosed with clinical early-stage endometrial cancer from 2015 to 2017. All patients were randomly assigned to receive a mixture of ICG and Tc99 with or without blue dye. Subgroup analysis for detection rates was performed for each group (double versus triple tracer). Results: One hundred and fifty-seven patients met the inclusion criteria. Eighty patients received ICG and Tc99 with unilateral and bilateral SLN detection rates of 97.5% and 81.3%, respectively. Seventy-seven patients received all three tracers with unilateral and bilateral detection rates of 93.5% and 80.5%, respectively. Only one patient in the triple tracer group was detected by blue dye alone. No significant differences were noticed in unilateral or bilateral detection rates between the two groups, nor in the detection of lymph node metastasis. Conclusion: The addition of blue dye to ICG and Tc99 did not demonstrate any improvement in SLN detection.